Ferrite Decarburization of High Silicon Spring Steel in Three Temperature Ranges - Zhao F.; Zhang C.L.; Liu Y.Z. (Archives of Metallurgy and Materials, 2016)
Surface decarburization of high silicon spring steel in ambient air was studied. The experimental results confirmed the decarburized mechanism under AC1 temperature, in the temperature range of AC1-AC3 and AC3-G. Under AC1 temperature, pearlite spheroidization and surface decarburization are carried out simultaneously and pearlite spheroidization is reinforced. Considering the oxidation loss depth, the “true ferrite decarburized depth” at 850 °C (AC3-G) is still smaller than that at 760°C (AC1-AC3). That is because an “incubation period” must pass away before ferrite decarburization occurs in the temperature range of AC3-G, and the ferrite decarburized rate is limited to being equal to the partial decarburized rate.